Pendekatan STBM Pilar I dalam Upaya Perubahan Perilaku Buang Air Besar Sembarangan pada Masyarakat - Katiandagho, Dismo; Mokoginta Jusran; Joy V.I. Sambuaga; Steven J. Soenjono; Agus Rokot (CV. CENDIKIA JENIUS INDONESIA, 2025)
The results of the initial survey and the results of interviews with health center officers, where there are still people who behave like they defecate in the river, and there are residents' houses close to the river, the final disposal of toilets is the river, this adds to the pollution river which is in Silian I Village. The aim of the activity is to carry out the STBM pillar I approach to change bowel behavior hazard in the community of Silian 1 Village, Southeast Minahasa Regency. The method of implementing community service is to provide training on STBM Pillar I and build a model toilet for the community. The intervention carried out provided training for STB Pillar I with the results being a change in community behavior in disposing of feces, so that STBM Pillar I can be realized, and a model toilet was built as a public toilet so that people who do not have a toilet can dispose of feces in the toilet. Conclusion: there was a change in the behavior of defecating carelessly from the community of Silian I Village and the community disposed of feces using a toilet.